Biosynthesis of Silver Nanoparticles using Ajuga iva leaf extract and evaluating their antibacterial activity against E. coli and Streptococcus Bacteria - Sasi, Mariam Mohammed; Eshkourfu, Rabia Omar; Amara, Rokaya Omar; Hribesh, Samira Omar (European Scientific Journal, ESJ, 2025)
Silver nanoparticle synthesis from plant extracts has been widely used in medicine. Potential applications of silver nanoparticles include wound dressings, prosthetic and surgical instrument coatings, drug delivery, and an antimicrobial agent. The present study prepared and tested an aqueous extract of Ajuga iva leaves for its phytochemical components. The results of the phytochemical analysis of Ajuga iva leaf extract revealed the presence of alkaloids, carbohydrates, proteins, flavonoids, phenols, saponins, and coumarins. Silver nanoparticles were synthesized using the Ajuga iva leaf extract in a 1 mM solution of silver nitrate. The synthesized silver nanoparticles were characterized with UV-Vis spectroscopy, X-ray diffraction (XRD), Scanning Electron Microscopy (SEM), Energy-dispersive X-ray spectroscopy (EDX), and Fourier Transform Infra-Red (FTIR) spectrum. SEM analysis revealed the size of the AgNPs of 36 nm, 55 nm, 70 nm, 100 nm, and 300 nm. The EDX study showed that the optical absorption peak was detected at 3 keV, the characteristic peak for the absorbed metallic silver nanoparticles. FTIR analysis identified the possible functional group involved in the reduction of silver metal ions into silver nanoparticles. In addition, the antibacterial activity of synthesized silver nanoparticles was also examined and the results showed good antibacterial activities against E. coli and Streptococcus bacteria.